(untitled) (Revista Electrónica de Didáctica en Educación Superior, 2017)
Como parte del proceso continuo de revisión de los procedimientos de evaluación en un curso masivo de Química, en este trabajo describimos: a) las ventajas de adoptar un sistema de calificación de ítems equivaluados con una grilla de correspondencia para exámenes parciales y b) la sistematización del análisis preliminar de resultados a fin de complementar y orientar mejoras académico-administrativas en varios niveles: grupos de trabajo puntuales, sedes específicas y generales del curso. Palabras clave: evaluación; química; curso masivo; análisis An analysis of formal evaluations in a massive chemistry course Considering the procedures of student evaluation in a massive course of Chemistry as an ongoing process, here we describe: a) the advantages of adopting a marking system of partial exams based on equivalent valued items and a qualification correspondence grid, and b) the use of statistical tools to provide more insight of the results, in order to improve academic-administrative tasks at various levels: specific work groups, specific teaching sites and the course as a whole. Keywords: evaluation; chemistry; massive course; analysis